APRESIASI MASYARAKAT TERHADAP MAKANAN DAN MINUMAN KAKI LIMA (STUDI KASUS MASYARAKAT DI SURAKARTA) - Nani Irma Susanti; Erna Tiningrum (BHIRAWA, 2013)
Foodandbeverages soldby PKL(street vendors) was onecontributor toa regionaleconomicturnaround. Although thebusinessunitwas smallbutwouldbe collectedwhenthe street vendorshada high valuefor the development ofregional.The data usedin this studywereprimary data takenwith a list ofquestions providedto the communityas asampleof 100 respondents.Testinstrumentanalyzingused, AnalysisRegression, t test, F test, testR2, and classical assumptionInstrumenttest resultsshowedallthe datawere valid and reliable. OfVariableRegressionanalysisSocial, Personaland Psychologicalshoweda positive influence onthe purchase decisionvariables. Variables thatmoststronglyinfluencedthepurchase decisionFoodandBeverageStreetinSurakartawasprivatevariable. Culturalvariableswhilenegativeaffect.Of thet testconcludedthat thevariableSocial, Personaland Psychologicalpositive and significant impactonFoodandBeveragePurchasingDecisionsStreetinSurakarta. Culturalvariableshad an influencewhile thenegativeandnot significant to theFoodandBeveragePurchasing DecisionsStreetinSurakarta. Keywords: Cultural, Social, andPsychologicalPersonalPurchase Decision